LICHEN METABOLISM IDENTIFIED IN EARLY DEVONIAN TERRESTRIAL ORGANISMS - Jahren A.H.; Porter S.; Kuglitsch J.J. (My University, 2003)
We used 13C values to identify lichen metabolism in the globally distributed Early Devonian (409-386 Ma) macrofossil Spongiophyton minutissimum, which had been alternatively interpreted as a green plant of bryophyte grade or as a lichen, based on its morphology. Extant mosses and hornworts exhibited a range of 13Ctissue values that was discrete from that of extant lichens. The 13Ctissue values of 96 S. minutissimum specimens coincided with 13Ctissue values of extant lichens. In contrast, S. minutissimum 13Ctissue values showed no similarity to bryophyte carbon isotope values. The identification of large global populations of lichens during the Early Devonian may indicate that lichen-accelerated soil formation fostered the development of Paleozoic terrestrial ecosystems.
Keywords: bryophyte; carbon isotope ratios; errestrial ecosystems; Spongiophyton minutissimum; lichen; Devonian; Paleozoic::Devonian; Палеозой::Девонская